The Effect of Family Support on the Quality of Life of Breast Cancer Patients Undergoing Chemotherapy at Aloei Saboe Hospital - Arsad, Nikmatisni; Abas, Alan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Family support is a form of interpersonal relationship that includes attitudes, actions and acceptance of family members, so that family members feel that someone cares. Results from interviews with breast cancer patients show that patients who have poor family support have a poor quality of life. The method used in this research is a quantitative method, using observation sheets. The sample in this study was the entire population undergoing chemotherapy at Aloei Saboe Hospital, totaling 53 patients. Data analysis uses the Simple Linear Regression test. This study showed results where there were 19 patients with good family support (35.8%), 9 patients (17%), and 25 patients (47.2%) who had good family support. The results of the analysis regarding the influence of family support on the patient's quality of life show that the p-value is (0.000). For the patient's family to provide more attention and support to other family members affected by breast cancer, for educational institutions, it is hoped that it can add journal references regarding quality of life and family support, future researchers should be able to add research variables so they can dig deeper into the quality of life of breast cancer patients with family support and for hospitals to establish policies or SOPs regarding the implementation of health education to patients and families regarding quality of life and the motivation that families must provide to patients.